Exclusive breastfeeding as a protective factor against overweight and obesity in children: A community-based study - Ahmad Iqbal Romdloni; Millennia Zulfa Salsabila; Julia Rosana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Childhood obesity is a prevalent global health problem. Overweight/obesity is abnormal and excessive accumulation of body fat caused by prolonged positive energy balance. Exclusive breastfeeding has shown its effectivity in reducing mortality in children and preventing diseases, including overweight/obesity. Purpose: To investigate the role of EBF as a protective factor against childhood overweight/obesity. Method: This study used retrospective case-control observational analytical approach. The target population included 126 children aged 12-59 months attending “Mother-Toddler Class” in March 2026. Breastfeeding history was evaluated using questionnaire adapted from 2017 IDHS while nutritional status was determined using WHO Child Growth Standards. Results: Analysis showed association between EBF and overweight/obesity in children was not statistically significant (p = 0.068). Nevertheless, EBF showed high clinical impact with 3.167-fold increased risk of overweight/obesity in non-exclusively breastfed infants (OR = 3.167). Conclusion: Despite the marginally significant association in this study, EBF remained beneficial in preventing overweight/obesity in children. Childhood obesity is a serious public health concern that requires national-level policies, with focus on promoting EBF and supporting healthy weight gain. Suggestion: National policies should focus on integrating supportive environments within workplace to ensure EBF. Standardized program like Mother-Toddler Class should be scaled nationally along with digitalization.